Transient Enhancement of Inhibitory Synaptic Transmission in Hippocampal CA1 Pyramidal Neurons after Cerebral Ischemia - Liang, Rui (2009)
Pyramidal neurons in hippocampal CA1 regions are highly sensitive to cerebral ischemia. Alterations of excitatory and inhibitory synaptic transmission may contribute to the ischemia-induced neuronal degeneration. However, little is known about the changes of GABAergic synaptic transmission in the hippocampus following reperfusion. We examined the GABA(A) receptor-mediated inhibitory postsynaptic currents (IPSCs) in CA1 pyramidal neurons 12 hours and 24 hours after transient forebrain ischemia. The amplitudes of evoked IPSCs (eIPSCs) were increased significantly 12 hours after ischemia and returned to control levels 24 hours following reperfusion. The potentiation of eIPSCs was accompanied by an increase of miniature IPSCs (mIPSCs) amplitude, and an enhanced response to exogenous application of GABA, indicating the involvement of postsynaptic mechanisms. Furthermore, there was no obvious change of the paired-pulse ratio (PPR) of eIPSCs and the frequency of mIPSCs, suggesting that the potentiation of eIPSCs might not be due to the increased presynaptic release. Blockade of adenosine A1 receptors led to a decrease of eIPSCs amplitude in post-ischemic neurons but not in control neurons, without affecting the frequency of mIPSCs and the PPR of eIPSCs. Thus, tonic activation of adenosine A1 receptors might, at least in part, contribute to the enhancement of inhibitory synaptic transmission in CA1 neurons after forebrain ischemia. The transient enhancement of inhibitory neurotransmission might temporarily protect CA1 pyramidal neurons, and delay the process of neuronal death after cerebral ischemia.